Benign Peripheral Nerve Sheath Tumor in a Wild Toco Toucan (Ramphastos toco) - Carvalho, Marcelo P. N.; Fernandes, Natalia C. C. A.; Nemer, Viviane C.; Neto, Ramiro N. Dias; Teixeira, Rodrigo H. F.; Miranda, Bruna S.; Mamprim, Maria J. [UNESP]; Catão-Dias, José L.; Réssio, Rodrigo A. (Association of Avian Veterinarians (AAV), 2016)
Peripheral nerve sheath tumors are a heterogeneous group of neoplasms that comprise neurofibromas, schwannomas, neurilemmomas, and perineuromas. In animals, peripheral nerve sheath neoplasms are most commonly diagnosed in dogs and cattle, followed by horses, goats, and cats, but their occurrence is uncommon in birds. An adult, free-living, male toco (common) toucan (Ramphastos toco) was admitted to the zoo animal clinic with weight loss, dehydration, and presence of a soft nodule adhered to the medial portion of the left pectoral muscle. Clinical, cytologic, and computed tomography scan results were indicative of a neoplasm. The toucan died during surgical resection of the mass. Necropsy, histopathologic, and immunohistochemical findings confirmed the diagnosis of benign peripheral nerve sheath tumor. To our knowledge, benign peripheral nerve sheath tumor has not previously been reported in a toucan or any other species in the order Piciformes.
Keywords: avian; bird; CD57; common toucan; immunohistochemistry; neoplasm; nodule; Piciformes; Ramphastos toco; toco toucan; wildlife